Identifikasi Dampak Pengelolaan Objek Wisata Dalam Mengurangi Tingkat Pengangguran Masyarakat Kabupaten Langkat - Nurrahman Nurrahman; Hendra Hermain (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The existence of tourism in Langkat Regency is very influential for the community in increasing economic resources to meet their daily needs. Apart from that, the increasing popularity of tourism is also very helpful in creating new jobs for people who initially had no work at all. The aim ofthis research is to find out whether the management of tourist attractions in Langkat Regency can reduce the unemployment rate in the area. This research uses a qualitative research approach. Researchers use a qualitative approach with the aim of uncovering data described by data sources and participants. The data validity technique for data validity used in this research is data triangulation. Source triangulation means re-checkingthe level of trustworthiness of information obtained from different sources. This research shows that the existence of tourism in Langkat Regency is very influential for the community in increasing economic resources to meet their daily needs. The impact felt by the community around tourist attractions is not only limited to increasing the income of business owners, but also empowering the local community more broadly bybuilding sustainable growth through the involvement of local communities in small business. Keywords: Tourist Attractions, Unemployment, Economic Improvement